New olenelloid trilobites from the Northwest Territories, Canada - Gapp, I. Wesley; Lieberman, Bruce S. (Zootaxa, 2014)
The Olenelloidea are a superfamily of early Cambrian trilobites, which have been the subject of several phylogenetic analyses and also used to address macroevolutionary questions regarding the nature and timing of the Cambrian radiation. The Sekwi Formation of the Mackenzie Mountains, Northwest Territories, Canada, has yielded numerous species from this clade, and here we present new information that expands on the diversity known from this biogeographically and biostratigraphically important region. In particular, we describe seven new species, (Olenellus baileyi, Mesonacis wileyi, Elliptocephala jaredi, Holmiella taurus, H. domackae, Mummaspis delgadoae, and Bristolia colberti). Also recovered are specimens of Elliptocephala logani, specimens that shared affinities with Olenellus clarki, O. getzi, O. fowleri, and Frizolenellus hanseni, and one partial specimen, which appears to be a new species of Bolbolenellus.